ANALISIS MODAL SOSIAL YANG DIKEMBANGKAN GURU EKONOMI DI SMA NEGERI KOTA PONTIANAK - Maria Ulfah; Munawar Thoharudin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractThis study aims to describe the social capital developed by economics teachers in Pontianak City High School. The approach used in this research is descriptive qualitative. Data was collected from 10 economics teachers in Pontianak City High School. Data analysis techniques using qualitative descriptive techniques. Data collection techniques used are interviews, observation and documentation and field notes / log books to see intellectual capital and social capital developed by economics teachers to improve the quality of graduates, and data collection instruments in the form: interviews to teachers about the social capital they develop and interviews with students and principals as a cross check data. It also observes the activities of teachers in developing social capital. The results showed that the social capital developed by economics teachers in Pontianak State High School includes Trust through the activities of teachers building mutual trust with their students in race activities. Keywords: Social Capital of Economic Teachers AbstrakPenelitian ini bertujuan untuk mendeskripsikan modal sosial yang dikembangkan guru ekonomi di SMA Negeri Kota Pontianak. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Data dikumpulkan dari 10 orang guru ekonomi SMA Negeri Kota Pontianak. Teknik análisis data menggunakan tehnik deskriptif kualitatif.Teknik pengumpulan data yang digunakan adalah dengan wawancara, observasi dan dokumentasi dan catatan lapangan /log book untuk melihat modal sosial yang dikembangkan oleh guru ekonomi untuk meningkatkan kualitas lulusan, dan Instrumen pengumpulan data berupa: wawancara kepada guru tentang modal social yang dikembangkannya serta wawancara dengan siswa dan kepala sekolah sebagai cros cek data. Selain itu juga melakukan pengamatan terhadap kegiatan guru dalam mengembangkan modal sosial. Hasil penelitian menunjukkan Modal sosial yang dikembangkan guru ekonomi di SMA Negeri Pontianak meliputi Trust melalui kegiatan guru-guru membangun rasa saling percaya dengan para siswanya dalam kegiatan perlombaan.Kata Kunci : Modal Sosial Guru Ekonomi